Islamic Social Finance and Institutional Accountability: A Case Study of Zakat and Philanthropic Organizations - Luhur Prasetiyo; Unun Roudlotul Janah; Khoirun Nisak (El-Barka, 2025)
Islamic Social Finance (ISF) significantly promotes social welfare, poverty alleviation, and inclusive economic development, particularly in Muslim-majority countries like Indonesia. This study investigates institutional accountability within Islamic philanthropic organizations managing Zakat, Infaq, Sadaqah, and Waqf (ZISWAF) in Ponorogo, Indonesia. Addressing gaps in the literature that mostly focus on national or international levels, this study emphasizes local governance challenges, the relationship between accountability and public trust, and the need for a Sharia-based accountability model. Employing a qualitative case study approach, data were collected through in-depth interviews, participant observation, and document analysis involving five Islamic philanthropic institutions. Thematic analysis revealed significant variations in financial accountability, Sharia compliance, and social accountability across institutions, highlighting the critical role of transparent reporting, external audits, and community engagement in enhancing public trust. The study proposes an integrated accountability model encompassing financial, Sharia, and social dimensions, advocating for enhanced digitalization, standardized Sharia audits, and improved public literacy to optimize ZISWAF fund management. These findings contribute to the theoretical discourse on Islamic social finance and provide practical recommendations for policymakers and practitioners aiming to strengthen institutional accountability and advance sustainable development goals.